Distribution, Magnitude and Adverse Effects of Invasive Vegetation in Garhwal Himalaya, Uttarakhand - Bisht, M. S.; Kukreti, Manish; Bhandari, Sunil; Bisht, Surjeet Singh; Dobriyal, A. K. (Indian Forester, 2012)
The present communication is about distribution, abundance and effects of three most common invasive plants Lantana, Eupatorium and Parthenium in district Chamoli and Pauri Garhwal of Uttarakhand, India. Findings of the survey conducted during the November 2008 and 2009 revealed that the invasive species has been well established in all ecological zones and habitats (except high altitudes above Â±2700m) of the area. The homogenization of these weed species was observed depleting the populations of many valuable native plant species as well as the wild life.